Brain Stimulation Exercises Using the Visual (Fit Light) Technique with Timing at Race Distances and their Effect on the Electrical Activity of the Rectus Femoris Muscles of 400-Meter Runners - Shaima Al-Azzawi (Jurnal Ilmiah Sport Coaching and Education, 2025)
ABSTRACT The study aimed to prepare brain stimulation exercises using the visual (Fit Light) technique with timings at race distances after being divided into four consecutive and continuous stages. Then, it aimed to identify its effect on the electrical activity of the rectus femoris muscles of 400-meter runners. The experimental method was adopted with a one-group design, involving eight elite runners from first-division clubs in Iraq. They were all intentionally selected from their original community at a rate of 100%. The researcher distributed (4) devices of the (Fit Light) technology, which operate with daylight (LED) lighting or twilight lighting, distributed over race distances of 100, 200, 300, and 400 meters. They are illuminated with high brightness before the runner reaches 10 meters for each distance. The work continued with the training during the special preparation period for competitions for (10) consecutive training weeks at a rate of (3) training units each week. The researcher also adopted the EMG device with a Bluetooth transmitter using two sensors for each rectus femoris muscle on the right and left. To obtain EMG signal results by reading both the peak and the area for each of the muscles at distances of (300) and (400) meters from the race using two systems of the EMG device, each placed in front of the specified distance. After completing the experiment with pre-measurement, application of the technique, and post-measurement, the researcher verified the results using SPSS. The conclusions and applications indicate that applying brain stimulation training using the visual (Fit Light) technique at timed intervals over the race distances improves the peak of the electrical signal activity (EMG). Also, it reduces the area in both the right and left rectus femoris muscles of the elite 400-meter runners. Based on these results, the researcher recommends that first-class athletics clubs should pay attention to developing the expertise of their employees on how to apply the (Fit Light) visual technology, in a manner that is appropriate and compatible with modernity in this field, so that these training methods suit the specificity of elite (400) meter runners.  Keywords: Fit Light, Technology, EMG device, Training  ABSTRAK Penelitian bertujuan untuk mempersiapkan latihan stimulasi otak menggunakan teknik visual (Fit Light) dengan pengaturan waktu sesuai jarak perlombaan setelah dibagi dalam empat tahap berturut-turut dan berkesinambungan. Kemudian bertujuan untuk mengetahui pengaruhnya terhadap aktivitas listrik otot rektus femoris pelari 400 meter. Metode eksperimental diadopsi dengan desain satu kelompok, yang melibatkan delapan pelari elit dari klub divisi satu di Irak. Mereka semua sengaja dipilih dari komunitas aslinya dengan tingkat 100%. Peneliti mendistribusikan (4) perangkat berteknologi (Fit Light) yang beroperasi dengan pencahayaan siang hari (LED) atau pencahayaan senja, didistribusikan pada jarak lomba 100, 200, 300, dan 400 meter. Mereka diterangi dengan kecerahan tinggi sebelum pelari mencapai 10 meter untuk setiap jarak. Pekerjaan dilanjutkan dengan pelatihan selama masa persiapan khusus untuk kompetisi selama (10) minggu pelatihan berturut-turut dengan kecepatan (3) unit pelatihan setiap minggunya. Peneliti juga mengadopsi perangkat EMG dengan pemancar Bluetooth menggunakan dua sensor untuk masing-masing otot rektus femoris di kanan dan kiri. Untuk memperoleh hasil sinyal EMG dengan membaca puncak dan luas masing-masing otot pada jarak (300) dan (400) meter dari perlombaan menggunakan dua sistem perangkat EMG yang masing-masing ditempatkan di depan jarak yang ditentukan. Setelah menyelesaikan percobaan dengan pra pengukuran, penerapan teknik, dan pasca pengukuran, peneliti memverifikasi hasilnya menggunakan SPSS. Kesimpulan dan penerapannya menunjukkan bahwa penerapan pelatihan stimulasi otak menggunakan teknik visual (Fit Light) pada interval waktu tertentu sepanjang jarak lomba meningkatkan puncak aktivitas sinyal listrik (EMG). Selain itu, hal ini juga mengurangi area otot rektus femoris kanan dan kiri pada pelari elit 400 meter. Berdasarkan hasil tersebut, peneliti menyarankan agar klub-klub atletik kelas satu hendaknya memperhatikan pengembangan keahlian para pegawainya tentang bagaimana penerapan teknologi visual (Fit Light), dengan cara yang sesuai dan sesuai dengan modernitas di bidang tersebut, sehingga metode latihan ini sesuai dengan kekhususan pelari elite (400) meter.  Kata Kunci : Fit Light, Teknologi, Alat EMG, Pelatihan